Mechanotransduction, nuclear architecture and epigenetics in Emery Dreifuss Muscular Dystrophy: tous pour un, un pour tous - Bianchi, Andrea (Nucleus, 2018)
The alteration of the several roles that Lamin A/C plays in the mammalian cell leads to a broad spectrum of pathologies that – all together – are named laminopathies. Among those, the Emery Dreifuss Muscular Dystrophy (EDMD) is of particular interest as, despite the several known mutations of Lamin A/C, the genotype–phenotype correlation still remains poorly understood; this suggests that the epigenetic background of patients might play an important role during the time course of the disease. Historically, both a mechanical role of Lamin A/C and a regulative one have been suggested as the driving force of laminopathies; however, those two hypotheses are not mutually exclusive. Recent scientific evidence shows that Lamin A/C sustains the correct gene expression at the epigenetic level thanks to the Lamina Associated Domains (LADs) reorganization and the crosstalk with the Polycomb Group of Proteins (PcG). Furthermore, the PcG-dependent histone mark H3K27me3 increases under mechanical stress, finally pointing out the link between the mechano-properties of the nuclear lamina and epigenetics. Here, we summarize the emerging mechanisms that could explain the high variability seen in Emery Dreifuss muscular dystrophy.